Hearing aids - Dillon, Harvey (Boomerang Press New York Thieme, 2012)
Completely revised to reflect the research and technological advances of the last decade, Hearing Aids, Second Edition contains new chapters on directional microphones and the latest digital signal processing strategies and provides readers with extensive coverage of all aspects of open-canal, thin-tube hearing aids.